Fibrin thrombi in deceased donor kidneys: Prevalence and influence on graft function and graft survival in transplanted patients. Issue 1 (20th November 2017) - Hansen, Ditte; Rørvig, Sara; Andersen, Claus B.; Sørensen, Søren S.
Abstract : Fibrin thrombi (FT) are occasionally found in the pre‐implantation biopsy of kidneys from deceased donors. The aim of this study was to monitor the prevalence and answer the question whether FT has any impact on future graft function in a Danish patient cohort. We looked for FT in all donor kidney biopsies taken at the time of renal transplantation in a Danish transplantation unit during a 10‐year period. Every recipient transplanted with a FT donor kidney (n = 15) were matched with up to five control recipients (n = 69), and graft function and graft survival were assessed. FT was present in 3% of the transplanted donor kidneys. Graft function was reduced in the FT group 6 months after transplantation (median estimated glomerular filtration rate (eGFR): 29 mL/min vs 46 mL/min; p = 0.017), but at 12 months, an apparent difference did not reach statistical significance. More patients were on dialysis in the FT group after 12 months compared with the control group (27% vs 6%; p = 0.049). In conclusion, FT in donor kidney biopsies at time of transplantation is a risk factor for the development of reduced renal function during the first year of transplantation.